Nilai Wajar Saham Sektor Advertising, Printing, dan Media Di Bursa Efek Indonesia - Edy Suryadi; Nur Fitria (JURNAL MANAJEMEN MOTIVASI, 2014)
The background of this research there is an indication that the stock price on the market does not showthe actual value of the shares, especially shares subsectors advertising, Printing, and Media. The intrinsicvalue of shares can be searched by using fundamental analysis of the company through the method ofdividend discount models (DDM). This research is a case study in which the withdrawal of a sample usingpurposive sampling. the data used are secondary data obtained from documents Indonesia StockExchange through its website www.idx.co.id. This research resulted in the intrinsic value of the shares ofthe sub sectors of advertising, Printing and Media, which found that the price of the shares of the subsectors of advertising, Printing, and the media in a state of high market prices (overvalued). Informationfor investors on the stock return is calculated through the method of capital asset pricing model (CAPM)and the formation of the portfolio as well as information for investors that the shares owned byPT.Jasuindo Tiga Perkasa has the highest return and can be considered for investment.